2015
DOI: 10.1007/s10803-015-2365-1
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Coherent Motion Processing in Autism: Is Dot Lifetime an Important Parameter?

Abstract: Contrasting reports of reduced and intact sensitivity to coherent motion in autistic individuals may be attributable to stimulus parameters. Here, we investigated whether dot lifetime contributes to elevated thresholds in children with autism. We presented a standard motion coherence task to 31 children with autism and 31 typical children, with both limited and unlimited lifetime conditions. Overall, children had higher thresholds in the limited lifetime condition than in the unlimited lifetime condition. Yet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 38 publications
2
23
1
Order By: Relevance
“…It is possible that the unlimited dot lifetime condition was too easy compared to the limited dot lifetime condition, resulting in all participants scoring significantly better and not allowing for a differentiation to be made based on AQ score. Similar results were obtained by Manning et al (2015), who used dot lifetimes of 83 versus 1000 ms and found no moderating effect of dot lifetime. Jackson et al (2013) used dot lifetimes of 80 and 300 ms and did find an AQ by dot lifetime interaction, supporting this explanation.…”
Section: The Degree Of Autistic Traits and Visual Perceptionsupporting
confidence: 86%
“…It is possible that the unlimited dot lifetime condition was too easy compared to the limited dot lifetime condition, resulting in all participants scoring significantly better and not allowing for a differentiation to be made based on AQ score. Similar results were obtained by Manning et al (2015), who used dot lifetimes of 83 versus 1000 ms and found no moderating effect of dot lifetime. Jackson et al (2013) used dot lifetimes of 80 and 300 ms and did find an AQ by dot lifetime interaction, supporting this explanation.…”
Section: The Degree Of Autistic Traits and Visual Perceptionsupporting
confidence: 86%
“…Similar results were obtained by Manning et al (2015), who used dot lifetimes of 83 versus 1000 ms and found no moderating effect of dot lifetime. Jackson et al (2013) used dot lifetimes of 80 and 300 ms and did find an AQ by dot lifetime interaction, supporting this explanation.…”
Section: The Degree Of Autistic Traits and Visual Perceptionsupporting
confidence: 86%
“…However, the other part of this literature, in which unlimited lifetime of the moving dots is employed, demonstrate intact performance in RDKs in ASD (e.g., Davis et al, 2006 ; Yamasaki et al, 2011 ; Chen et al, 2012 ; for the short display duration of 220 ms). It has been recently shown that typically developed individuals and those diagnosed with ASD are equally affected by the dot lifetime (Manning et al, 2015 ).…”
Section: Global Motion Processingmentioning
confidence: 99%